Analisis Struktur dan Kebahasaan Feature Perjalanan (Travelogue Feature) Dalam Detik.Com Serta Rekomendasinya Sebagai E-Modul Teks Berita Ringan Kelas VII SMP - Putri, Anisa Noviani; Setiawan, Hendra; Hartati, Dian (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research was motivated by the development of news in online media that can be utilized as alternative reading. The objectives of this research include: (1) to describe the structure of travelogue features in Detik.com, (2) to describe the language of travelogue features in Detik.com, and (3) to compile the results of the analysis of the structure and language of travelogue features in Detik.com as e-modules of soft news texts and recommend them to students of grade VII in junior high school. This research uses qualitative descriptive method. The subject of this research is travelogue features in Detik.com, specifically 16 travelogue features to West Java tourist attractions from the travel section of DetikJabar in the March 2022-2023 edition. The objects of this research include: (1) the structure of travelogue features; and (2) the language of travelogue features. Data collection techniques, namely documentation with listening and recording techniques. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results showed that the sixteen travel features in Detik.com fulfill the completeness of the structure with the title, intro, body, and closing arranged systematically. As for the sixteen travel features in Detik.com, the linguistic characteristics are informal, interesting, simple, brief, and use active sentences. Thus, it can be concluded that the structure and language of travel features in Detik.com are in accordance with the rules of feature writing. The results of the analysis are then compiled as e-modules of light news texts and recommended to seventh grade students.